In-season training model for National Association of Intercollegiate Athletics female basketball players using "microdosed" programming - Bonder, I.; Shim, A. (Strength and Conditioning Journal, 2023)
Basketball is an intermittent-intensity sport requiring sufficient levels of muscular strength and power to display successful performance. To achieve high levels of performance, proficiency must be attained in jumping/repeated jump ability, sprinting/repeated sprint ability, change of direction/agility, and basketball-specific skills. The "in-season" period during a National Association of Intercollegiate Athletics female basketball team comprises more than 6 months of the annual plan, making it the longest uninterrupted training "`block" throughout the year. However, no more than 3 hours per day may be allotted for practice, skill work, and training. Because of competition, travel, and academic obligations, little time may be available for training. The purpose of this article is to provide a time-efficient, in-season training plan using microdosing programming methodology directed at improving muscular strength and power. In turn, improvements in strength and power will be the foundation of developing traits specific to successful basketball performance and reducing chances of injury. In addition, methods to monitor individual daily fatigue are provided.